Elevated platelet-derived growth factor-BB concentrations in premature neonates who develop chronic lung disease - Adcock Kim G; Martin Jeremy; Loggins John; Kruger Thomas E; Baier R John (BMC, 2004)
Abstract Background Chronic lung disease (CLD) in the preterm newborn is associated with inflammation and fibrosis. Platelet-derived growth factor-BB (PDGF-BB), a potent chemotactic growth factor, may mediate the fibrotic component of CLD. The objectives of this study were to determine if tracheal aspirate (TA) concentrations of PDGF-BB increase the first 2 weeks of life in premature neonates undergoing mechanical ventilation for respiratory distress syndrome (RDS), its relationship to the development of CLD, pulmonary hemorrhage (PH) and its relationship to airway colonization with Ureaplasma urealyticum (Uu). Methods Infants with a birth weight less than 1500 grams who required mechanical ventilation for RDS were enrolled into this study with parental consent. Tracheal aspirates were collected daily during clinically indicated suctioning. Uu cultures were performed on TA collected in the first week of life. TA supernatants were assayed for PDGF-BB and secretory component of IgA concentrations using ELISA techniques. Results Fifty premature neonates were enrolled into the study. Twenty-eight infants were oxygen dependent at 28 days of life and 16 infants were oxygen dependent at 36 weeks postconceptual age. PDGF-BB concentrations peaked between 4 and 6 days of life. Maximum PDGF-BB concentrations were significantly higher in infants who developed CLD or died from respiratory failure. PH was associated with increased risk of CLD and was associated with higher PDGF-BB concentrations. There was no correlation between maximum PDGF-BB concentrations and Uu isolation from the airway. Conclusions PDGF-BB concentrations increase in TAs of infants who undergo mechanical ventilation for RDS during the first 2 weeks of life and maximal concentrations are greater in those infants who subsequently develop CLD. Elevation in lung PDGF-BB may play a role in the development of CLD.